What Business Managers Should Know About Quantum Computing? - Kelvin Leong; Anna Sung (Journal of Interdisciplinary Sciences)
Business management requires rapid reactions to the changes of business environment effectively. Given quantum computing’s game-changing power will bring huge transformation, therefore managers should be aware of how to take the advantage of quantum computing and recognize its potential impacts to the business world. In fact, quantum computing will deliver exponential advantages for various problems, such as factoring very large numbers within very short time, therefore it has dramatic impacts on existing business issues, such as cybersecurity practice, business optimization, investment decision making, search from unstructured data, etc. However, although the topic is emerging, only very limited studies have been conducted with specific focus on the potential impacts of quantum computing on business management. Accordingly, this study was conducted to fill this knowledge gap. In this study, we began with analyzing quantum related investment markets, trends in scholarly publication and keyword search on the internet about quantum computing. In addition, we provided an introduction on what is quantum computing and discussed related quantum algorithms. Finally, we summarized four major potential applications of quantum computing in business management. Hopefully this paper can serve as a reference for researchers, industrial participators and policy makers engaged in future research or practical applications on related topics.